THE ILO CONVENTION NO. 190 CONCERNING THE ELIMINATION OF VIOLENCE AND HARASSMENT AT WORK: REASONS FOR RATIFICATION - Dragićević, Marija; Obradović, Goran (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2024)
Although it is mentioned many times in the regulations of the International Labor Organization, the issue of violence and harassment at work has not, until recently, been the immediate and main topic of any convention of this important international organization. Therefore, Violence and Harassment Convention No. 190 is extremely important, since it is the first and only international legal instrument that directly addresses violence and harassment at work. In addition, this Convention has an extremely wide scope in terms of persons and areas to which it applies. Its aim is to provide protection to employees and others against violence and harassment at work in all sectors, whether private or public, in the formal or informal economy, in urban or rural areas. In this paper, the authors discuss Convention No. 190, its basic characteristics and definitions, its scope, and the manner in which the procedure for preventing and protecting against violence and harassment at work is regulated. After that, the authors assess whether, given the existing level of legal protection of employees and other workers against violence and harassment at work in the Republic of Serbia, such an act is necessary for our country, and if so, what new and better things it would bring to our legal system and the protection of workers compared to the current situation.